2009
DOI: 10.1080/15459620903418746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IOM Personal Sampler at Different Flow Rates

Abstract: The Institute of Occupational Medicine (IOM) personal sampler is usually operated at a flow rate of 2.0 L/min, the rate at which it was designed and calibrated, for sampling the inhalable mass fraction of airborne particles in occupational environments. In an environment of low aerosol concentrations only small amounts of material are collected, and that may not be sufficient for analysis. Recently, a new sampling pump with a flow rate up to 15 L/min became available for personal samplers, with the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Before the experiment, the glass-fiber filters fixed in the cassette were carefully weighed with a microbalance (ME, Sartorius, Göt-tingen, Germany). The air flow of the pump (4 l/min) was calibrated with the Gilibrator-2 (Gilian, Sensidyne, Schauenburg International GmbH, Mülheim, Germany) [14].…”
Section: Gravimetrical Analysis Of Supra-micron (>1 M) Respirable Dustmentioning
confidence: 99%
“…Before the experiment, the glass-fiber filters fixed in the cassette were carefully weighed with a microbalance (ME, Sartorius, Göt-tingen, Germany). The air flow of the pump (4 l/min) was calibrated with the Gilibrator-2 (Gilian, Sensidyne, Schauenburg International GmbH, Mülheim, Germany) [14].…”
Section: Gravimetrical Analysis Of Supra-micron (>1 M) Respirable Dustmentioning
confidence: 99%
“…[15] Anthony et al [17] reported that computerized simulations of the new sampler operating at a flow rate of 10 L/min also achieved the targeted sampler efficiency. Zhou et al [16] researched the effect of increasing the flow rate of an IOM sampler from 2 L/min to 10.6 L/min in order to evaluate if the performance of the sampler was similar at both flow rates. Using a wind tunnel, they evaluated the sampling efficiency of the IOM sampler as it pertained to particle size, wind speed, and wind direction.…”
Section: Introductionmentioning
confidence: 99%
“…Using a wind tunnel, they evaluated the sampling efficiency of the IOM sampler as it pertained to particle size, wind speed, and wind direction. [16] Zhou and his colleagues concluded that at a low wind speed of 0.56 m/s, the IOM could maintain its original collection capabilities while operated at a higher flow rate. They found that the direction-averaged sampling efficiencies for both flow rates had a similar trend, but there was a slightly lower efficiency for the 10.6 L/min sampling flow rate as compared with that of the 2 L/min flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the schematic diagram of the Lovelace Respiratory Research Institute (LRRI) large wind tunnel facility employed in this research. This wind tunnel facility has been used in many sampler performance studies for different stationary and personal aerosol samplers (Cheng et al, 2004;Irshad et al, 2006;Zhou and Cheng, 2010), and the results acquired have shown that this wind tunnel can provide reliable experimental data for general aerosol sampler evaluation studies. The LRRI large wind tunnel consists of an 11-m circular duct (1.8 m in diameter), an array of industrial gas mixing blenders (Blender Products, Inc. Denver, CO), a honeycomb flow straightener, a 4.3 m (L) Â 3.7 m (W) Â 3.6 m (H) test chamber, a outflow HEPA filter bank, and a 50-hp motor (Marathon Electric, Wausau, WI).…”
Section: Wind Tunnelmentioning
confidence: 99%